Astrocyte arachidonate and palmitate uptake and metabolism is differentially modulated by dibutyryl-cAMP treatment. (July 2016) - Seeger, D.R.; Murphy, C.C.; Murphy, E.J.
Abstract: Astrocytes play a vital role in brain lipid metabolism; however the impact of the phenotypic shift in astrocytes to a reactive state on arachidonic acid metabolism is unknown. Therefore, we determined the impact of dibutyryl-cAMP (dBcAMP) treatment on radiolabeled arachidonic acid ([1- 14 C]20:4n-6) and palmitic acid ([1- 14 C]16:0) uptake and metabolism in primary cultured murine cortical astrocytes. In dBcAMP treated astrocytes, total [1- 14 C]20:4n-6 uptake was increased 1.9-fold compared to control, while total [1- 14 C]16:0 uptake was unaffected. Gene expression of long-chain acyl-CoA synthetases ( Acsl ), acyl-CoA hydrolase ( Acot7 ), fatty acid binding protein(s) ( Fabp ) and alpha-synuclein ( Snca ) were determined using qRT-PCR. dBcAMP treatment increased expression of Acsl3 (4.8-fold) and Acsl4 (1.3-fold), which preferentially use [1- 14 C]20:4n-6 and are highly expressed in astrocytes, consistent with the increase in [1- 14 C]20:4n-6 uptake. However, expression of Fabp5 and Fabp7 were significantly reduced by 25% and 45%, respectively . Acot7 (20%) was also reduced, suggesting dBcAMP treatment favors acyl-CoA formation. dBcAMP treatment enhanced [1- 14 C]20:4n-6 (2.2-fold) and [1- 14 C]16:0 (1.6-fold) esterification into total phospholipids, but the greater esterification of [1- 14 C]20:4n-6 is consistent with the observed uptake through increased Acsl, but not Fabp expression. Although total [1- 14 C]16:0 uptake was not affected, there was a dramatic decrease in [1- 14 C]16:0 in the free fatty acid pool as esterification into the phospholipid pool was increased, which is consistent with the increase in Acsl3 and Acsl4 expression. In summary, our data demonstrates that dBcAMP treatment increases [1- 14 C]20:4n-6 uptake in astrocytes and this increase appears to be due to increased expression of Acsl3 and Acsl4 coupled with a reduction in Acot7 expression. Highlights: dBcAMP treatment increases arachidonate uptake into astrocytes. dBcAMP treatment increases arachidonate and palmitate targeting into phospholipids in astrocytes. dBcAMP treatment increases gene expression of Acsl3 and 4 in astrocytes. dBcAMP treatment reduces gene expression of Acot7 in astrocytes.